The Right to Housing: During and After the Covid-19 Pandemic - Bohdan Fasii; Andrii Levytskyi; Andrii Savytskyi (Universidad Hemisferios, 2021)
The importance of ensuring the right to housing during the pandemic Covid-19 and avoiding its negative impact on all spheres of human life is multifaceted. In particular, the least protected sections of the population, who often do not have their housing at all, usually are deprived of the opportunity to follow the rules of social distance and suffer more than others from the disease. Unsatisfactory living conditions during the period of complete quarantine and the need to stay at home all the time, indirectly affect the mental state of people and cause quarrels, domestic violence, and other problems of their residents. The purpose of the study is to establish the constitutive elements of the right to housing as a basic constitutional right, and to find ways of legal foundation of this right. The subject of the study are national and international regulations that ensure the right to housing, decisions of national and international courts, and constitutional doctrine. The research methods were philosophical, general scientific, and special scientific methods such as system-structural, comparative and formal methods. As a result of the study, the authors of the article came to the conclusion that the right to housing should be provided both at the level of national and international regulations. Scholars and legislators need special attention to ensuring the housing rights of vulnerable groups. Government subsidies and benefits are key to both the poor affected by the pandemic and businesses that are forced to lose profits.